PENGARUH BRAND IMAGE DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN SEPATU LOKAL MEREK COMPASS - WISNU YUSDITARA; HANNA MEILANI DAMANIK; MARTIN LUTER PURBA; HENDRIK E.S. SAMOSIR (LP2MTBM MAKARIOZ, 2022)
This study aims to see how the influence of brand image and promotion to influence consumer purchasing decisions on local shoes brand Compass. This study uses a snowball sampling method on respondents aged 20-34 years in the city of Medan. The results of the study conclude that the brand image built by Compass has a positive impact on increasing purchasing decisions for Compass brand shoes, it means that the positive influence caused is not visible. The promotion variable carried out by Compass has a positive impact on increasing purchasing decisions for branded shoe products, the impact of this promotion also significantly affects the decisions of potential consumers.